The Role of Environmental Costs, Managerial Ownership, and Financial Performance in Driving Corporate Social Responsibility: Evidence from Indonesia’s Basic Materials Industry - Nadia Octaviani; Faiza Muklis (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
This study aims to examine the effect of environmental costs, managerial ownership, and financial performance on corporate social responsibility (CSR). The research employs a quantitative approach using secondary data obtained from the Indonesia Stock Exchange (IDX). The population consists of companies in the basic materials sector listed on the IDX for the 2022–2024 period, with 16 firms selected through purposive sampling. The dependent variable in this study is CSR, while the independent variables are environmental costs, managerial ownership, and financial performance. Panel data regression analysis was conducted using EViews 12. The results indicate that environmental costs and financial performance positively and significantly affect CSR, while managerial ownership has a negative effect. The coefficient of determination (R²) of 39.83% suggests that the independent variables explain 39.83% of the variation in CSR, while the remaining 60.17% is influenced by other factors outside the model.